Beyond Enrollment: Unpacking the Dropout Crisis in Nepalese Universities - Joshi, Rajendra Prasad; Chand, Gambhir Bahadur (Journal of Tikapur Multiple Campus, 2026)
Dropout is defined as the act of leaving an educational institution or program before its completion or university without earning the degree. This is reflecting as a growing trend in the universities and higher institutions in Nepal. This study is an attempt to find out the major causes behind the students' dropout from university courses and to find the solutions to this growing trend. The research adopted a mixed-method research design. The quantitative data were collected from forty teachers involved in teaching and learning at Tribhuvan University and Far Western University using a Google Form with questions that had multiple checkboxes to choose from. The collected data were analyzed using simple statistical tools. For the qualitative information, the researchers asked open-ended questions and conducted a focus group discussion among ten teachers selected using a purposive non-random sampling procedure. The collected data were then analyzed to find out the themes of the causes and solutions to the dropout. Significant findings suggested that migration abroad, academic failure or difficulty, financial hardships, and family responsibilities, a mismatch between students’ expectations and the college environment, heavy-loaded course content, and the duration of the academic degree are the significant causes of the students' dropout. To reduce the dropout, counseling and job placement support, curriculum update, collaboration with industries, connecting learning to earning, and providing scholarships and financial aid to the students are measures that can be applied to reduce the dropout of students.